(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the organization of the foreign policy management in England in the 60-70s of the XIX century and factors, which influenced it are investigated. The degree of the monarchís, the prime ministerís, parliamentís, pressís influence on the process of acceptance and realization of foreign policy decisions is defined. The detailed characteristics of the management organization of foreign policy in England, in the centre and on places, in this period are given. As a result it was found out that the monarch and the prime minister pretended on the management of English foreign policy and tried to control the activity of the head of Foreign office. The diplomatic service in England at that period was professional.